Enhanced magneto dielectric effect on oxygen annealed geometrically frustrated spin-chain compound: Ca3Co2O6. (September 2019) - Meera, K.; Muralidharan, R.; Koo, T.Y.; Jeong, Y.H.
Abstract: In the present work we report on the magneto dielectric studies of oxygen annealed, one dimensional compound Ca3 Co2 O6 . The magnetic and electrical properties were studied on the polycrystalline samples prepared by conventional solid state reaction method and annealed in oxygen atmosphere. The magnetization versus temperature curve shows paramagnetic behavior up to 30 K and interesting magnetic transitions below that temperature. A dielectric anomaly around 15 K was observed. The change in dielectric constant between 75 K and 100 K is not intrinsic and is due to the grain boundary contributions in the polycrystalline sample. Our results predict that annealing at oxygen atmosphere improve the physical properties of calcium cobaltates which are promising materials for magnetoelectric applications. Graphical abstract: Image 1 Highlights: We report on the annealing effect on magneto dielectric properties of a one dimensional spin chain compound, Ca3 Co2 O6 . It shows profound anomaly in dielectric constant near the magnetic transition temperature. There is obvious difference in the physical properties of as sintered and oxygen annealed samples. Our manuscript predicts that oxygen annealing might be prerequisite for these kinds of samples.